ANALISIS PERGERAKAN SAHAM, OBLIGASI DAN EMAS SEBAGAI DASAR PENGKAJIAN EMAS SEBAGAI HEDGING DAN SAFE HAEVN - , Pratika Adi Nugraheni ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The objective of this research is to analysis market movement of gold, bond and stock to investigate the existence of a safe haven and a hedge. A safe haven is defined as asset that is uncorrelated with stocks and bonds in case of a market crash. A hedge is defined as a asset that is uncorrelated with stocks and bonds on average. The sample of this study are daily returns of gold, bond and stock over 2007-2009 period with applying Generalized AutoRegressive Conditional Heteroscedasticity (GARCH).